Synthesis and Biological Activity of Silver Nanoparticles from Medicinal Palm Tree Bismarckia nobilis Seeds - Alam, Tanveer; Tyagi, Sapna; Kumar, Goutam; Khan, Azhar; Chauhan, Neha; Tarannum, Hina; Ahmad, Parwez; Rizvi, A. (Asian Journal of Chemistry, 2020)
Silver nanoparticles (AgNPs) have received significant attention due to their distinctive antimicrobial, anticancer, catalytic and photochemical activity. The objective of this work is to amalgamate silver nanoparticles from the aqueous extract of Bismarckia nobilis seeds using green method, characterization using UV-visible spectroscopy, X-ray diffraction, transmission electron microscopy and FTIR spectroscopy. Further, its antimicrobial and anticancer activities were evaluated. The results displayed the characteristic UV peak, cubic phase with crystalline nature, spherical in shape having average size 14 nm, prominent peaks of bio-functional groups, good antimicrobial and anticancer activities.